Developing Winning Brand Strategies - Finskud, Lars (Business Expert, 2012)
Every manager knows that robust strategy plays a crucial role in any enterprise. Yet, for all the publications that have been written on the subject, three things remain true. Strategy is complex, many companies still get it wrong, and driving organic growth in maturing markets is increasingly challenging. Existing tools and approaches have been valuable but increasingly tend to be insuffi cient for identifying growth in today’s mature and competitive markets. It is only through developing detailed understanding, with a fairly high level of granularity, of what actually drives brand performance and how these drivers can be infl uenced that incremental growth opportunities become clear. Developing Winning Brand Strategies introduces, at a high level, the actual relationships between branding, strategy, and corporate performance. It provides a fresh perspective on, and approach for, developing robust customer-focused strategy and describes the important role of the brand in competing successfully for stakeholder choice. Consumer choice does not materialize spontaneously. To win, companies need to ascertain how consumers choose and churn between competing brands, what drives their brands’ selection, and how to target effectively in order to recruit new consumers while retaining existing ones. Brands play a pivotal role in this process: They are the vehicles, or focal points, that businesses use in competing for choice. The proposition, qualities, image, and values that businesses embed in their brands are the basis for winning customer loyalty. However, to compete for choice isn’t easy. Today’s rapidly changing world of industry deregulation, growing competitive intensity, newly empowered consumers, and multiple stakeholders means that management must make decisions about how to recruit and retain stakeholders under conditions that are complex and dynamic. Despite this, companies frequently develop strategy on the basis of intuition rather than solid fact. Developing Winning Brand Strategies adds signifi cant value providing a holistic, in-depth understanding of the business dynamics and consumers’ selection criteria enabling management to make informed strategic decisions.The Competing for Choice approach described in this book has been developed through years of research and practice. It has proven to be a great success for leading or challenging branded companies worldwide in creating and sustaining growth for their business, regardless of industry. It enables senior managers to rethink strategy and allocate their investments more effectively—and radically improve business performance as a result.